Psychological Risk Factors among Transgender: The Mediating Role of Body Dissatisfaction between Quality of Life, Suicidal Ideation and Social Interaction Anxiety: Psychological Risk Factors among Transgender - batool, iram; bakhtawer, sobia; Saher, Noreen; Batool, Huma (South Asian Journal of Social Sciences and Humanities, 2022)
AbstractSocial attitudes, prejudice and stigmas towards transgender community vary around the world. Consequently, the prevalence of suicidal attempts, self-injurious behaviors, and associated psychological factors were very common among them. The current study aimed to examine the association between quality of life, suicidal ideation, social interaction anxiety and body image among trans genders. Two hundred trans genders of age between 18-45 years participated in this study. They were approached by using snow ball sampling technique from different cities of Pakistan. Four instruments, Body Image States Scale (BISS), World Health Organization Quality of Life Scale- (WHOQOL-BREF), Beck Scale for Suicidal Ideation (BSSI), Social Interaction Anxiety (SIA) were used in this research. The results showed no significant difference on demographic variables with regard to body image, social interaction anxiety, quality of life and suicidal ideation (p
Keywords: Quality of life; suicidal ideation; social interaction anxiety; body image; transgender